Association between Preoperative Plasma sRAGE Levels and Recovery from Cardiac Surgery - Benedict C. Creagh-Brown; Gregory J. Quinlan; Lauren R. Hector; Timothy W. Evans; Anne Burke-Gaffney (Mediators of Inflammation)
Background. The receptor for advanced glycation end products (RAGE) is an inflammation-perpetuating receptor, and soluble RAGE (sRAGE) is a marker of cellular RAGE expression. This study investigated whether raised plasma levels prior to surgery of sRAGE or S100A8/A9 (a RAGE ligand) were associated with longer duration of hospital care in patients undergoing cardiac surgery necessitating cardiopulmonary bypass. Methods. Patients (n=130) undergoing elective cardiac surgery were enrolled prospectively. Plasma sRAGE and S100A8/A9 concentrations were measured before and 2 h after surgery. Results. Preoperative plasma sRAGE increased significantly (P<0.0001) from 1.06 ng/mL (IQR, 0.72–1.76) to 1.93 ng/mL (IQR, 1.14–2.63) 2 h postoperatively. Plasma S100A8/9 was also significantly (P<0.0001) higher 2 h postoperatively (2.37 μg/mL, IQR, 1.81–3.05) compared to pre-operative levels (0.41 μg/mL, IQR, 0.2–0.65). Preoperative sRAGE, but not S100A8/A9, was positively and significantly correlated with duration of critical illness (r=0.3, P=0.0007) and length of hospital stay (LOS; r=0.31, P<0.0005). Multivariate binary logistic regression showed preoperative sRAGE to be, statistically, an independent predictor of greater than median duration of critical illness (odds ratio 16.6, P=0.014) and to be, statistically, the strongest independent predictor of hospital LOS. Conclusion. Higher preoperative plasma sRAGE levels were associated with prolonged duration of care in adults undergoing cardiac surgery requiring cardiopulmonary bypass.